Correlation between MBL2/CD14/TNF-α gene polymorphisms and susceptibility to spinal tuberculosis in Chinese population. Issue 1 (2nd February 2018) - Zheng, Mingfeng; Shi, Shiyuan; Wei, Wei; Zheng, Qi; Wang, Yifan; Ying, Xiaozhang; Lu, Di
Abstract : Objective: The present study investigated the clinical significance of mannose-binding lectin 2 (MBL2), cluster of differentiation 14 (CD14) and tumour necrosis factor-α (TNF-α) gene polymorphisms in patients with spinal tuberculosis (TB) in Chinese population. Methods: A total of 240 patients with spinal TB were enrolled in the present study from May 2013 to August 2016 at Hangzhou Red Cross Hospital. A total of 150 age- and sex-matched healthy subjects were enrolled as controls. The genomic DNA was extracted from the peripheral blood of all subjects, and the MBL2, CD14 and TNF-α gene polymorphisms were detected by direct DNA sequencing. Results: (1) Compared with controls, patients with spinal TB exhibited a significantly higher frequency of the XY genotype at the −221G>C polymorphism as well as the Q allele and PQ genotype or an association with the QQ genotype at the +4C>T polymorphism in the MBL2 gene. (2) Compared with controls, patients with spinal TB exhibited a significantly higher frequency of the T allele and TT genotype or an association with the CT genotype at the −159C>T polymorphism in the CD14 gene. (3) Compared with controls, patients with spinal TB exhibited a significantly higher frequency of the T allele and the CT genotype or an association with the TT genotype at the TNF-857 polymorphism in the TNF-α gene. Conclusion: The −221G>C polymorphism of MBL2, the −159C>T polymorphism of CD14 and the TNF-857 polymorphism of TNF-α are risk factors for spinal TB and may be involved in the development of spinal TB in the Chinese population. These factors are indicators of susceptibility to spinal TB and require clinical attention.